microRNA-1471 suppresses glioma cell growth and invasion by repressing metadherin expression - Meng, Liang (Int J Clin Exp Pathol, 2018)
microRNA-1471 (miR-1471) is a newly identified miRNA that is downregulated in breast cancer. However, its biological roles in human tumors are largely unknown. This study aimed to investigate the clinical significance and functions of miR-1471 in glioma. We found miR-1471 expression was significantly reduced in glioma tissues and cell lines. Forced expression of miR-1471 remarkedly suppressed glioma cell proliferation and invasion. Notably, metadherin (MTDH) was validated as a direct target of miR-1471 and the restoration of MTDH expression reversed the inhibitory effects of miR-1471 on glioma cell proliferation and invasion. Also, low miR-1471 expression was a predictor for worse 5-year overall survival of glioma patients. Overall, these results reveal the tumor suppressive role of miR-1471 in glioma, highlighting the potential to consider miR-1471/MTDH axis as a therapeutic target for the treatment of glioma in the near future.